Interlanguage interference of the Azerbaijani and Turkish languages: ways to address the problem (linguistic approach & teaching practice) - Zh. F. Aliyeva; F. A. Dursunova; A. V. Shtanov (Дискурс профессиональной коммуникации, 2020)
One of the core aspects the methodology of teaching foreign languages focuses on is the issue of interlanguage interference. In this paper it is referred to as some kind of a controversy between the primary and secondary linguistic personalities at the early stages of the latter. This is explained by the dominant nature of the native language compared to the foreign one and is represented:• at the formal level by the mechanical transfer of a certain form of the original native language from one of its levels – phonetic, lexical or grammatical, or• at the associative level of meanings and concepts – while constructing speech in a foreign language, one trensfers the association from the native one; this association is foregrounded within the framework of specific speech conceptual and semantic connections and is relevant for the native language, but senseless for the foreign one.As a rule, calquing results in consequences of different semantic complexity – from blocking a certain speech fragment in a foreign language due to its complete meaninglessness, to inaccuracy and semantic distortion.Interlanguage interference manifests itself differently in different language pairs. For a research it is important to understand how languages of the corresponding pair relate to each other – whether languages are completely different genealogically and typologically; or matching either genealogically or typologically; or closely related both genealogically and typologically. The aim of the paper is to study the interference in a pair of closely related languages: Azerbaijani & Turkish, where the former is native and the latter is foreign. This is a special case for study, since the significant similarity of the two languages, though providing many positive results, gives an absolutely specific type of interference. İt requires a detailed analysis in order to overcome the negative impact of the mother tongue on a foreign language in the process of foreign language acquisition.